Formaldehyde sensing using tapered u-shape plastic optical fiber coated with zinc oxide nanorods - Tiu, Zian Cheak; Johari, Siti Halma; Abdul Rahim, Hazli Rafis; Md Johari, Md Ashadi; Mohd Yusof, Haziezol Helmi; Jali, Mohd Hafiz; Harun, Sulaiman Wadi (Institute Of Electrical And Electronics Engineers Inc., 2022)
Continuous exposure to formaldehyde may cause injury to the central nervous, respiratory, blood, and immunological systems. Tapered U-shape plastic optical fiber (POF) coated with zinc oxide nanorods was evaluated at wavelength of 645 nm for formaldehyde vapor sensing within a concentration range from 5% to 20%. The tapered POF with 500 µm waist diameter was prepared using chemical etching technique. Zinc oxide nanorods were synthesized using hydrothermal method and growth for 12 hours on the tapered POF. The proposed sensor exhibited a good response to formaldehyde concentration ranging from 5% to 20% with sensitivity and linearity measured to be 0.00543V/% and 98.58%, respectively. Excellent measurement stability was observed when the concentrations from 5% and above are maintain over a 600 second period. Highest difference voltage was produced by 0.0958V due to the more scattering effect of ZnO nanorods at 20% of formaldehyde concentration. This proposed sensor might be also used to detect air pollution produced not just by formaldehyde vapor, but also by other dangerous or poisonous vapors or gases.